Aloe gel modified aqueous binder as well as preparation method and application thereof
By using aloe vera gel water system binders, the problem of low capacity density density and poor circulation stability caused by lithium sulfur batteries due to loss of sulfur active substances and lithium anode corrosion during the cycle, which realized higher actual than actual comparison than Energy density and more stable cycle performance.
Patent Information
- Application Number
- CN202411270243.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-21
AI Technical Summary
During the circulation process, the actual specific capacity density is low and the circulation stability is poor due to the loss of sulfur active substances and the corrosion of the lithium anode.
The water -based adhesive with aloe vera was modified. This adhesive consists of aloe vera gel and acidic acid. Through the cross -linked reaction modification, a bonding agent with good mechanical properties and viscosity piece.
Effectively suppress the shuttle effect of multi -sulfide, reduce the volume changes in the cycle, and improve the actual energy density and cycle stability of lithium sulfur batteries.
Smart Images

Figure CN119331569A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium-sulfur battery material preparation, and in particular to an aloe vera gel-modified aqueous binder and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have broad market prospects in portable electronic devices and great potential for application in electric vehicles. With the increase in power consumption and the demand for vehicle range, future batteries should have high energy density, fast charging capability, safety and environmentally friendly composition materials. In this regard, lithium-sulfur (Li-S) batteries have a high energy density of 1675 mAh g due to the environmentally friendly, naturally abundant and economically efficient positive electrode material sulfur (S). -1 High theoretical capacity and 2600Wh·kg -1 The high energy density of lithium-sulfur batteries makes them one of the most promising next-generation energy storage systems. However, from the perspective of practical application, the practicality of lithium-sulfur batteries still faces huge obstacles. One of the most critical obstacles is that during the cycle, the sulfur active substance is reduced to lithium sulfide intermediates, which dissolve and diffuse in the electrolyte, resulting in a shuttle effect that causes the loss of active substances, resulting in a low actual specific capacity density. In addition, the lithium anode will also be severely corroded, resulting in a decrease in coulombic efficiency and a reduction in the capacity and cycle stability of the battery.
[0003] In order to overcome the problem of low specific energy density, researchers around the world have proposed various cathode modification strategies, such as encapsulating sulfur active materials with different types of conductive carbon carriers such as porous carbon, hollow carbon, disordered carbon nanotubes, double-shell hollow carbon spheres, etc. However, since the selection of different carbon hosts requires complex steps and high costs, we need a simple and easy strategy to improve the electrochemical performance of sulfur cathodes.
[0004] As we all know, the electrode sheet is composed of active materials, conductive agents, binders and current collectors. As an important component of the positive electrode sheet of the battery, the binder is used in small amounts, but it is also crucial to the electrochemical performance of the electrode. Traditional polyvinylidene fluoride (PVDF) binders are not good at improving the electrochemical performance of the sulfur cathode, especially under high sulfur loading, due to their insufficient mechanical properties, weak adhesion, and poor restraint of polysulfides. In order to address the negative effects of PVDF, various polymers with polar functional groups have been used as sulfur cathode binders. Due to their strong adhesion and adsorption of polysulfides, they have shown great potential.
[0005] Therefore, it is crucial to design and develop a cathode with good mechanical properties and viscosity that can effectively inhibit the shuttle effect of soluble polysulfides and reduce the volume change during the cycle, thereby improving the problem of low actual specific energy density of the sulfur cathode. Summary of the invention
[0006] The purpose of the present invention is to provide an aloe vera gel-modified aqueous adhesive and a preparation method and application thereof, so as to solve the technical problems raised in the background technology.
[0007] To achieve the above object, the present invention provides the following technical solution: an aloe vera gel-modified aqueous adhesive, comprising aloe vera gel and phytic acid;
[0008] The aloe vera gel is extracted from the stems and leaves of aloe vera;
[0009] The mass content of phytic acid is 5wt% to 45wt%.
[0010] A method for preparing an aloe vera gel-modified aqueous adhesive comprises at least the following steps:
[0011] S1: preparing aloe vera gel, washing the stems and leaves of aloe vera, removing the tips, roots and epidermis of the aloe vera leaves, cutting them into small pieces, putting them into a juicer and blending them, letting them stand for 2 hours to defoam, filtering them with filter cloth to remove large volume residues, centrifuging them to obtain the supernatant, and then freeze-drying the supernatant for 48 hours to obtain an aloe vera gel sample;
[0012] S2: cross-linking with phytic acid, cross-linking the aloe vera gel sample obtained in S1 with phytic acid, and freeze-drying the solution for 48 hours after the reaction is completed;
[0013] S3: Take out the dried sample in S2, add deionized water, and stir until the aloe vera gel is completely dissolved. The mass concentration is 20 mg mL -1 of adhesive.
[0014] Furthermore, the temperature of the cross-linking reaction in S2 is 25° C. to 55° C., and the time of the cross-linking reaction in S2 is 2 h to 6 h.
[0015] The invention discloses an application of an aloe vera gel-modified water-based binder, and the aloe vera gel-modified water-based binder is used for preparing a positive electrode plate of a lithium-sulfur battery.
[0016] A lithium-sulfur battery positive electrode plate comprises a positive electrode active material, a conductive agent and a binder, wherein the binder is an aloe vera gel-modified aqueous binder.
[0017] Furthermore, the positive electrode active material is elemental sulfur;
[0018] The conductive agent includes any one of carbon black, conductive carbon and graphene.
[0019] A preparation method for a positive electrode of a lithium-sulfur battery comprises at least the following steps:
[0020] Mixing the positive electrode active material, the conductive agent and the binder uniformly;
[0021] Add deionized water to form a slurry and stir for more than 12 hours;
[0022] The slurry is then coated on a carbon-coated aluminum foil and vacuum dried at 60° C. for 24 hours to obtain a positive electrode sheet for a lithium-sulfur battery.
[0023] Furthermore, the mass ratio of the positive electrode active material, the conductive agent and the binder is 7:2:1.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention provides an aloe vera gel-modified aqueous binder, which is extracted from natural aloe vera stems and leaves, and an aloe vera gel sample is obtained by washing, peeling, crushing, filtering, centrifuging, freeze-drying and other steps, and then the aloe vera gel sample and phytic acid are cross-linked and modified according to a certain mass ratio (wherein the mass content of cross-linked phytic acid in the binder is 5-45wt%). The aloe vera leaves have the advantages of being inexpensive, easy to obtain, natural, environmentally friendly and easy to extract, thereby reducing the cost of the binder; the natural green plant aloe vera gel contains a large number of polar groups, which has a strong chemical adsorption capacity and stable mechanical properties for polysulfides; a large number of oxygen-containing functional groups contained in the binder react with phosphate groups in phytic acid to form stable chemical bonds, which can effectively restrain polysulfides and avoid shuttle effects.
[0026] 2. The present invention also provides a lithium-sulfur battery positive electrode plate, which adopts the binder of the present invention. When the positive electrode plate prepared by the binder is used in a lithium-sulfur battery, since the binder has good mechanical properties, it is also conducive to adapting to the volume expansion caused by the battery during the charging and discharging process. Therefore, the prepared battery has better bonding strength and stability, reduces the electrode damage caused by volume expansion during the charging and discharging cycle, and plays an indispensable role in improving the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0028] Figure 1 A comparison chart of the cycle performance of lithium-sulfur batteries using the positive electrode sheet (S@AG / PA-1) of a lithium-sulfur battery prepared in Example 5 and the positive electrode sheet (S@AG / PA-2) of a lithium-sulfur battery prepared in Example 6;
[0029] Figure 2A comparison chart of the cycle performance of lithium-sulfur battery positive electrode sheets (S@AG / PA-2, S@AG / PA-3, S@AG / PA-4) prepared in Examples 6 to 8 and the lithium-sulfur battery positive electrode sheet (S@AG) prepared in Comparative Example 1 when applied to lithium-sulfur batteries;
[0030] Figure 3 The lithium-sulfur battery positive electrode sheet (S@AG / PA-3) prepared in Example 7 and the lithium-sulfur battery positive electrode sheets (S@PVDF, S@CMC) prepared in Comparative Examples 2 to 3 are applied to the cycle performance comparison diagram (a) and the charge and discharge voltage curve comparison diagram (b) of lithium-sulfur batteries;
[0031] Figure 4 Comparison of cyclic voltammetry curves of lithium-sulfur battery positive electrode sheet (S@AG / PA-3) prepared in Example 7, lithium-sulfur battery positive electrode sheet (S@CMC) prepared in Comparative Example 2 using carboxymethyl cellulose (CMC) as a binder, and lithium-sulfur battery positive electrode sheet (S@PVDF) prepared in Comparative Example 3 using polyvinylidene fluoride (PVDF) as a binder, applied to lithium-sulfur batteries. Among them, (a) is the cyclic voltammetry curve of S@AG / PA-3, (b) is the cyclic voltammetry curve of S@CMC, and (c) is the cyclic voltammetry curve of S@PVDF;
[0032] Figure 5 The positive electrode sheet (S@AG / PA-3) of a lithium-sulfur battery prepared in Example 7, the positive electrode sheet (S@CMC) of a lithium-sulfur battery prepared using carboxymethyl cellulose (CMC) as a binder in Comparative Example 2, and the positive electrode sheet (S@PVDF) of a lithium-sulfur battery prepared using polyvinylidene fluoride (PVDF) as a binder in Comparative Example 3 are applied to rate performance diagrams of lithium-sulfur batteries;
[0033] Figure 6 The SEM images of carbon-coated aluminum foil after being immersed in phytic acid (PA) solution for 12 hours. (a) is the SEM image of 5wt% PA after being immersed for 12 hours, (b) is the SEM image of 25wt% PA after being immersed for 12 hours, and (c) is the SEM image of 45wt% PA after being immersed for 12 hours.
[0034] Figure 7 The morphology of the electrode sheet prepared by the binder under SEM. (a) is the SEM image of the positive electrode sheet (S@AG / PA-3) of the lithium-sulfur battery prepared in Example 7, (b) is the SEM image of the positive electrode sheet (S@CMC) of the lithium-sulfur battery prepared by using carboxymethyl cellulose (CMC) as the binder in Comparative Example 2, and (c) is the SEM image of the positive electrode sheet (S@PVDF) of the lithium-sulfur battery prepared by using polyvinylidene fluoride (PVDF) as the binder in Comparative Example 3;
[0035] Figure 8The figures are structural analysis and mechanical property comparison diagrams of the binder, wherein (a) is an infrared spectrum comparison of AG of Comparative Example 1 and AG / PA-3 prepared in Example 3, and (b) is a 180° peeling test result comparison diagram of the positive electrode sheet (S@AG / PA-3) of the lithium-sulfur battery prepared in Example 7, the positive electrode sheet (S@CMC) of the lithium-sulfur battery prepared with carboxymethyl cellulose (CMC) as a binder in Comparative Example 2, and the positive electrode sheet (S@PVDF) of the lithium-sulfur battery prepared with polyvinylidene fluoride (PVDF) as a binder in Comparative Example 3;
[0036] Fig. 9 The O1s high-resolution XPS spectra of the binder AG / PA-3 prepared in Example 3 after absorbing ultraviolet light, wherein (a) is an ultraviolet absorption spectrum, (b) is an N1s high-resolution XPS spectrum of the binder AG / PA-3 before adsorbing polysulfide, and (c) is an N1s high-resolution XPS spectrum of the binder AG / PA-3 after adsorbing ultraviolet light. ;
[0037] Fig.10 Schematic diagram of the electrochemical performance of the prepared lithium-sulfur battery after 300 cycles at a current density of 0.5C when AG was cross-linked and modified by OA, D-AA and Tau and used as a binder for the positive electrode of a lithium-sulfur battery. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0039] An aloe vera gel-modified aqueous adhesive, the adhesive is composed of aloe vera gel and phytic acid (the cross-linked phytic acid content in the adhesive is 5-45wt%), and deionized water is added to prepare 20mg·mL -1 The binder has a mass concentration of 5wt%, 25wt%, or 45wt% of cross-linked phytic acid, and the cross-linking conditions are 25°C, 40°C, or 55°C, and the reaction time is 2h, 4h, or 6h.
[0040] Example 1
[0041] An aloe vera gel-modified aqueous adhesive, the adhesive is composed of aloe vera gel and phytic acid (the cross-linked phytic acid content in the adhesive is 5wt%). The specific preparation method is as follows:
[0042] (1) Take fresh Aloe vera stems and leaves, wash them with deionized water and remove the tip, root and epidermis of the aloe leaves;
[0043] (2) After crushing, filtering, centrifuging, and freeze-drying for 48 hours, an aloe vera gel sample was obtained;
[0044] (3) Weigh 0.95 g of the aloe vera gel sample in step (2) and 0.05 g of phytic acid, add deionized water and stir magnetically at 40° C. for 2 h to carry out a cross-linking reaction. After the reaction is completed, freeze-dry the solution for 48 h;
[0045] (4) Take 0.20 g of the dried sample in step (3), add 10 mL of deionized water and stir until completely dissolved, so that the solution mass concentration is 20 mg mL -1 , and prepare an aloe vera gel-modified aqueous adhesive (AG / PA-1).
[0046] Example 2
[0047] An aloe vera gel-modified aqueous adhesive, the adhesive is composed of aloe vera gel and phytic acid (the cross-linked phytic acid content in the adhesive is 5wt%). The specific preparation method is as follows:
[0048] (1) Take fresh Aloe vera stems and leaves, wash them with deionized water and remove the tip, root and epidermis of the aloe leaves;
[0049] (2) After crushing, filtering, centrifuging, and freeze-drying for 48 hours, an aloe vera gel sample was obtained;
[0050] (3) Weigh 0.95 g of the aloe vera gel sample in step (2) and 0.05 g of phytic acid, add deionized water and stir magnetically at 40° C. for 4 h to carry out a cross-linking reaction. After the reaction is completed, freeze-dry the solution for 48 h;
[0051] (4) Take 0.20 g of the dried sample in step (3), add 10 mL of deionized water and stir until completely dissolved, so that the solution mass concentration is 20 mg mL -1 , and prepare an aloe vera gel-modified aqueous adhesive (AG / PA-2).
[0052] Example 3
[0053] An aloe vera gel-modified aqueous adhesive, the adhesive is composed of aloe vera gel and phytic acid (the cross-linked phytic acid content in the adhesive is 25wt%). The specific preparation method is as follows:
[0054] (1) Take fresh Aloe vera stems and leaves, wash them with deionized water and remove the tip, root and epidermis of the aloe leaves;
[0055] (2) After crushing, filtering, centrifuging, and freeze-drying for 48 hours, an aloe vera gel sample was obtained;
[0056] (3) Weigh 0.75 g of the aloe vera gel sample in step (2) and 0.25 g of phytic acid, add deionized water and stir magnetically at 40° C. for 4 h to carry out a cross-linking reaction. After the reaction is completed, freeze-dry the solution for 48 h;
[0057] (4) Take 0.20 g of the dried sample in step (3), add 10 mL of deionized water and stir until completely dissolved, so that the solution mass concentration is 20 mg mL -1 , and prepare an aloe vera gel-modified aqueous adhesive (AG / PA-3).
[0058] Example 4
[0059] An aloe vera gel-modified aqueous adhesive, the adhesive is composed of aloe vera gel and phytic acid (the cross-linked phytic acid content in the adhesive is 45wt%). The specific preparation method is as follows:
[0060] (1) Take fresh Aloe vera stems and leaves, wash them with deionized water and remove the tip, root and epidermis of the aloe leaves;
[0061] (2) After crushing, filtering, centrifuging, and freeze-drying for 48 hours, an aloe vera gel sample was obtained;
[0062] (3) Weigh 0.55 g of the aloe vera gel sample in step (2) and 0.45 g of phytic acid, add deionized water and stir magnetically at 40° C. for 4 h to carry out a cross-linking reaction. After the reaction is completed, freeze-dry the solution for 48 h;
[0063] (4) Take 0.20 g of the dried sample in step (3), add 10 mL of deionized water and stir until completely dissolved. The mass concentration of the solution is 20 mg mL -1 , and prepare an aloe vera gel-modified aqueous adhesive (AG / PA-4).
[0064] Example 5
[0065] A positive electrode plate for a lithium-sulfur battery, the positive electrode plate comprising elemental sulfur as a positive electrode active material, conductive carbon black and the binder AG / PA-1 in Example 1. The specific preparation method thereof is as follows:
[0066] The positive electrode active material elemental sulfur, conductive carbon black and the binder AG-1 in Example 1 were ground and mixed in a mass ratio of 7:2:1, deionized water was added to form a slurry and stirred for more than 12 hours, the slurry was coated on a carbon-coated aluminum foil with a scraper, and then transferred to a vacuum oven and dried for 24 hours to obtain a lithium-sulfur battery positive electrode sheet (S@AG / PA-1).
[0067] Example 6
[0068] A positive electrode plate for a lithium-sulfur battery, the positive electrode plate comprising elemental sulfur as a positive electrode active material, conductive carbon black and the binder AG / PA-2 in Example 2. The specific preparation method thereof is as follows:
[0069] The positive electrode active material elemental sulfur, conductive carbon black and the binder AG-2 in Example 2 were ground and mixed in a mass ratio of 7:2:1, deionized water was added to form a slurry and stirred for more than 12 hours, the slurry was coated on a carbon-coated aluminum foil with a scraper, and then transferred to a vacuum oven and dried for 24 hours to obtain a lithium-sulfur battery positive electrode sheet (S@AG / PA-2).
[0070] Example 7
[0071] A positive electrode plate for a lithium-sulfur battery, the positive electrode plate comprising elemental sulfur as a positive electrode active material, conductive carbon black and the binder AG / PA-3 in Example 3. The specific preparation method thereof is as follows:
[0072] The positive electrode active material elemental sulfur, conductive carbon black and the binder AG-3 in Example 3 were ground and mixed in a mass ratio of 7:2:1, deionized water was added to form a slurry and stirred for more than 12 hours, the slurry was coated on a carbon-coated aluminum foil with a scraper, and then transferred to a vacuum oven and dried for 24 hours to obtain a lithium-sulfur battery positive electrode sheet (S@AG / PA-3).
[0073] Example 8
[0074] A positive electrode plate for a lithium-sulfur battery, the positive electrode plate comprising elemental sulfur as a positive electrode active material, conductive carbon black and the binder AG / PA-4 in Example 4. The specific preparation method thereof is as follows:
[0075] The positive electrode active material elemental sulfur, conductive carbon black and the binder AG-4 in Example 4 were ground and mixed in a mass ratio of 7:2:1, deionized water was added to form a slurry and stirred for more than 12 hours, the slurry was coated on a carbon-coated aluminum foil with a scraper, and then transferred to a vacuum oven and dried for 24 hours to obtain a lithium-sulfur battery positive electrode sheet (S@AG / PA-4).
[0076] Comparative Example 1
[0077] The positive electrode active material elemental sulfur, conductive carbon black and pure aloe vera gel (AG) binder are ground and mixed evenly in a mass ratio of 7:2:1, deionized water is added to form a slurry and stirred for more than 12 hours, the slurry is coated on a carbon-coated aluminum foil with a scraper, and then transferred to a vacuum oven for drying for 24 hours to obtain a lithium-sulfur battery positive electrode sheet (S@AG).
[0078] Comparative Example 2
[0079] The positive electrode active material elemental sulfur, conductive carbon black and commercially available sodium carboxymethyl cellulose (CMC) binder are ground and mixed in a mass ratio of 7:2:1, deionized water is added to form a slurry and stirred for more than 12 hours, the slurry is coated on a carbon-coated aluminum foil with a scraper, and then transferred to a vacuum oven for drying for 24 hours to obtain a lithium-sulfur battery positive electrode sheet (S@CMC).
[0080] Comparative Example 3
[0081] The positive electrode active material elemental sulfur, conductive carbon black and commercially available polyvinylidene fluoride (PVDF) binder are ground and mixed evenly in a mass ratio of 7:2:1, deionized water is added to form a slurry and stirred for more than 12 hours, the slurry is coated on a carbon-coated aluminum foil with a scraper, and then transferred to a vacuum oven and dried for 24 hours to obtain a lithium-sulfur battery positive electrode sheet (S@PVDF).
[0082] Performance Testing
[0083] 1. Comparison of the cycle performance of the lithium-sulfur battery positive electrode sheets prepared in Example 5 and Example 6 in lithium-sulfur batteries
[0084] In a button CR2032 battery mold, from the negative electrode to the positive electrode, the negative electrode shell, a lithium sheet with a diameter of 12 mm and a thickness of 0.6 mm, a diaphragm (celgard2300) with a diameter of 16 mm, and a positive electrode sheet with a diameter of 8 mm (the positive electrode sheet is the positive electrode sheet of the lithium-sulfur battery prepared in Example 5 or Example 6) are stacked in sequence, and then 30 μL of commercial lithium-sulfur battery electrolyte (1M LiIFSI dissolved in a DOL / DME mixed solvent containing 2wt.% LiNO3, the volume ratio of DOL / DME is 1:1) is dripped to the center of the electrode sheet, and then a baffle with a diameter of 16 mm, a gasket and a positive electrode shell are covered in sequence, and finally the button battery is sealed with a tablet press to assemble each lithium-sulfur battery. The two Li-S batteries obtained above were charged and discharged at a current of 0.5C (1C = 1675mA·g -1 ), the cycle performance test was carried out under the condition of charge and discharge voltage range of 1.5V-3V. The experimental results are as follows Figure 1 shown.
[0085] Depend on Figure 1 It can be seen that when AG / PA-1 and AG / PA-2 are used as binders for the positive electrode of lithium-sulfur batteries, the prepared lithium-sulfur batteries show good coulombic efficiency. Among them, the lithium-sulfur battery prepared by AG / PA-2 can provide 710.1mAh·g at a current density of 0.5C. -1 The initial specific capacity of AG / PA-1 was 2 hours, and it was able to maintain a stable electrochemical cycle during the subsequent cycles. In comparison, the corresponding battery of AG / PA-1 performed poorly. The reason is that the AG / PA-1 binder only cross-linked for 2 hours during the preparation process, and some functional groups failed to react with the hydrogen bonds in PA in time, while the AG / PA-2 binder, which cross-linked for 4 hours, had a more sufficient reaction time, so it showed better electrochemical performance. Subsequently, a binder that was cross-linked for 6 hours was added for the preparation of lithium-sulfur battery positive electrodes. The electrochemical performance test results were not much different from 4 hours, so the optimal cross-linking time was determined to be 4 hours.
[0086] 2. Comparative Examples 6 to 8 and the cycle performance of the lithium-sulfur battery positive electrode sheets prepared in Comparative Example 1 in lithium-sulfur batteries
[0087] The button cells were assembled according to the same experimental steps as above, except that the positive electrode sheets were replaced with the positive electrode sheets of the lithium-sulfur batteries prepared in Examples 6 to 8 and Comparative Example 1. The four obtained batteries were cycled for 300 cycles at 0.5C. The experimental results are shown in Figure 2 It can be clearly seen that the lithium-sulfur battery prepared by the lithium-sulfur battery positive electrode sheet (S@AG / PA-3) prepared in Example 7 not only has a higher initial specific capacity (1162.1 mAh·g -1 ), and after 300 cycles, it still has 731.8 mAh g -1 The specific capacity of the battery is maintained at a good stability. Although the electrochemical performance of the battery prepared by the lithium-sulfur battery positive electrode sheets (S@AG / PA-2 and S@AG / PA-4) prepared in Example 6 and Example 8 is not as good as that of S@AG / PA-2, it is significantly improved compared with the uncrosslinked comparative example 1 (S@AG).
[0088] 3. Electrochemical performance of the lithium-sulfur battery positive electrode sheets prepared in Comparative Example 7 and Comparative Examples 2 to 3 in lithium-sulfur batteries
[0089] Assemble button cells according to the same experimental steps as above, and replace the positive electrode sheets with the positive electrode sheets of lithium-sulfur batteries prepared in Example 7 and Comparative Examples 2-3. Figure 3 (a) shows the charge and discharge cycle efficiency of the three batteries at 0.5C for 300 cycles. It can be seen in the figure that the electrochemical performance of the lithium-sulfur battery prepared by the lithium-sulfur battery positive electrode sheet (S@AG / PA-3) prepared in Example 7 is significantly better than that of the lithium-sulfur battery prepared by the lithium-sulfur battery positive electrode sheets (S@CMC and S@PVDF) prepared in Comparative Examples 2 and 3. This is because the hydroxyl group and lithium polysulfide have a strong binding effect, which can effectively inhibit the shuttle effect. The charge and discharge performance test was carried out under the conditions of a charge and discharge current of 0.5C and a charge and discharge voltage range of 1.5V to 3V. The results are as follows: Figure 3(b) shows a comparison of the charge and discharge voltage curves of S@AG / PA-3, S@CMC and S@PVDF for lithium-sulfur batteries. It can be seen from the figure that the difference in the charge and discharge voltage platform of S@AG / PA-3 is △E=0.251V, the difference in the charge and discharge voltage platform of S@CMC is △E=0.309V, and the difference in the charge and discharge voltage platform of S@PVDF is △E=0.532V. That is, the ΔE value of S@AG / PA-3 is the smallest, which also proves that its polarization phenomenon is the smallest. The sulfur positive electrode using AG / PA-3 binder during the charge and discharge process is the most stable. In addition, the specific capacity of commercial CMC and PVDF binders during the charge and discharge cycle of lithium-sulfur batteries is much smaller than that of S@AG / PA-3, resulting in a low utilization rate of active sulfur, which shows that the aloe-modified water-based binder has certain advantages in practical application value.
[0090] The obtained battery was then subjected to a cyclic voltammetry test, and the experimental results are as follows: Figure 4 As shown, Figure 4 (a) Cyclic voltammetry curve of a lithium-sulfur battery prepared using the lithium-sulfur battery positive electrode sheet (S@AG / PA-3) prepared in Example 7; Figure 4 (b) Cyclic voltammetry curve of a lithium-sulfur battery prepared using the lithium-sulfur battery positive electrode sheet (S@CMC) prepared in Comparative Example 2; Figure 4 (c) is the cyclic voltammetry curve of the lithium-sulfur battery prepared by the lithium-sulfur battery positive electrode sheet (S@PVDF) prepared in Comparative Example 3. By comparison, when S@AG / PA-3 is used as a binder to prepare a lithium-sulfur battery, the difference in the redox peak position of the cyclic voltammetry curve is significantly smaller, and the peak current is higher. The reduction peaks of the first activation cycle appear at 2.02V and 2.29V, corresponding to the conversion of S8 into soluble high-order Li2S after further discharge reaction. X (4≤x≤8) and insoluble low-order Li2S2, Li2S. During the charging process, the oxidation peak at 2.40V also represents the reversible reaction of Li and S, and the position of the redox peak is well maintained after cycling. In addition, the voltage difference between charge and discharge of S@AG / PA-3 is small, indicating faster conversion kinetics. This is attributed to the fact that the rich polar functional groups of AG / PA-3 can effectively capture lithium polysulfides, reducing the polarization of the reaction.
[0091] In order to study the rate performance of the positive electrode sheet of the lithium-sulfur battery, the lithium-sulfur battery prepared by the positive electrode sheet (S@AG / PA-3) of the lithium-sulfur battery prepared in Example 7, the positive electrode sheet (S@CMC) of the lithium-sulfur battery prepared in Comparative Example 2 and the positive electrode sheet (S@PVDF) of the lithium-sulfur battery prepared in Comparative Example 3 were tested at a rate within the range of 0.5C to 4C. The experimental results are as follows: Figure 5The average specific capacity of S@AG / PA-3 at 0.5C, 1C, 2C and 4C is 1082 mAh·g -1 、925.4mAh·g -1 、802.6mAh·g -1 and 654.8mAh·g -1 , which is much higher than that of S@CMC and S@PVDF. When the current value increases to 4C, the discharge capacity of S@CMC and S@PVDF cathodes decreases to 360.3 mAh·g -1 and 276.8 mAh g -1 This indicates that the binder (AG / PA-3) prepared in Example 3 significantly improves the rate performance of the positive electrode sheet of the lithium-sulfur battery.
[0092] 4. Comparative Characterization of the Lithium-Sulfur Battery Positive Electrode Sheets Prepared in Comparative Example 7 and Comparative Examples 2 to 3
[0093] (1) SEM characterization
[0094] Since the cross-linking agent phytic acid (PA) is acidic, in order to investigate the negative effects of PA solutions with different mass fractions on the positive electrode, SEM tests were performed on carbon-coated aluminum foil after being immersed in 5-45wt% PA solutions for 12 hours. Figure 6 As shown, (a) is the carbon-coated aluminum foil after immersion in 5wt% PA for 12 hours, (b) is the carbon-coated aluminum foil after immersion in 25wt% PA for 12 hours, and (c) is the carbon-coated aluminum foil after immersion in 45wt% PA for 12 hours. As can be seen from the figure, as the mass fraction of the PA solution increases, the corrosion degree of the carbon-coated aluminum foil by the solution becomes more serious. It can be clearly seen that part of the carbon layer falls off on the aluminum foil with a mass fraction of 45wt%, while the corrosion degree of the carbon layer of the aluminum foil with 5wt% and 25wt% is roughly the same. Therefore, it can be indirectly explained that the higher the cross-linking concentration, the better the electrochemical performance of the battery. The negative effect of the cross-linking agent PA on the carbon-coated aluminum foil should be considered.
[0095] In order to explore the role of the binder in the electrode sheet, the surface morphology of the electrode sheet prepared based on the binder (AG / PA-3) prepared in Example 3 and the binders (CMC and PVDF) of Comparative Examples 2 and 3 was characterized by SEM. Figure 7 , (a) is the SEM image of the electrode sheet S@AG / PA-3, (b) is the SEM image of the electrode sheet S@PVDF, and (c) is the SEM image of the electrode sheet S@PVDF. It can be observed from the figure that some cracks appear on the surface of the S@CMC and S@PVDF cathodes. In contrast, at the same scale, the S@AG / PA-3 cathode is flatter and has fewer cracks, basically maintaining the integrity of the electrode, which further confirms that the AG / PA-3 binder can firmly bind the positive electrode materials together.
[0096] (2) Infrared spectrum and 180° peel strength
[0097] The present invention studies an aloe vera gel modified water-based adhesive. Infrared spectroscopy is used to study the interaction between AG and PA, such as Figure 8 (a) In the AG spectrum, the -1 The broad peaks at 1595, 1415 and 1236 cm belong to the stretching vibration of the OH bond. -1 The peaks at 1595, 1415 and 1236 cm-1 belong to the stretching vibrations of OCO, C=O and COC, respectively. With the addition of PA, the peaks of the binder (AG / PA-3) prepared in Example 3 increase from 1595, 1415 and 1236 cm-1 to 1595, 1415 and 1236 cm-1. -1 Transformed to 1603, 1452 and 1240 cm -1 , still at 1179cm -1 and 1010cm -1 New P=O and PO bonds were formed at the sites. The shift of these peaks indicates that there is a strong intermolecular interaction between AG and PA, and the newly formed chemical bonds prove that AG and PA are successfully cross-linked. This multiple interaction gives the AG / PA-3 adhesive strong mechanical properties. Figure 8 (b) shows the 180° peeling test results of the lithium-sulfur battery positive electrode sheet (S@AG / PA-3) prepared in Example 7, the lithium-sulfur battery positive electrode sheet (S@CMC) prepared with carboxymethyl cellulose (CMC) as a binder in Comparative Example 2, and the lithium-sulfur battery positive electrode sheet (S@PVDF) prepared with polyvinylidene fluoride (PVDF) as a binder in Comparative Example 3. According to the test results, it can be seen that the average peel strength of S@AG / PA-3 is about 3.12N, which is significantly higher than CMC (about 1.24N) and PVDF (about 0.98N), and there is no irregular fluctuation in the peeling curve, indicating that the adhesion of AG / PA-3 binder to the sulfur positive electrode is stronger than that of CMC and PVDF, and the enhanced adhesion strength is attributed to the cross-linking of the abundant phosphate groups of PA with the hydroxyl groups on AG to form a stable structure.
[0098] (3) UV absorption and XPS characterization
[0099] 0.0046g Li2S was added to 10ml DME. After it was fully dissolved, 0.016g S was added and heated and stirred overnight to make 10mmol·L -1 50 mg of the binder (AG / PA-3) prepared in Example 3 was taken and then placed in 4 ml of 1.5 mmol·L -1 After standing for 4 hours, the supernatant was taken and the ultraviolet absorption of visible light was measured at 350-600nm. The experimental results are as follows: Fig. 9 As shown in (a). Fig. 9In (a), it can be found that the UV absorbance of the polysulfide peak of AG / PA-3 is significantly reduced, showing a higher polysulfide absorbance, which indicates that the binder plays a beneficial role in suppressing the harmful shuttle effect to improve the stability and electrochemical performance of the derived sulfur cathode.
[0100] Fig. 9 (b) and (c) are the high-resolution XPS spectra of N1s before and after the binder AG / PA-3 adsorbed polysulfide and absorbed ultraviolet light. By comparing the two figures, it can be found that the binding energy of amino nitrogen, pyrrolic nitrogen, pyridinic nitrogen, graphitic nitrogen and nitrogen oxide all shifted to the low energy direction by about 0.3 to 0.5 eV. This result shows that the AG / PA-3 binder can chemically bond to lithium polysulfide and effectively limit its shuttle effect.
[0101] Similarly, the binders prepared in Examples 1 to 2 and Example 4 were subjected to the same performance tests as the binder prepared in Example 3, and similar experimental results were obtained, which once again proved that the binder prepared by modifying the plant gum extracted from Aloe vera has good mechanical properties, helps to alleviate large volume expansion, has strong ability to adsorb lithium polysulfide, and can effectively inhibit the shuttle effect of polysulfide. The corresponding binders were made into positive electrode sheets (Examples 5 to 6 and Example 8) and used in lithium-sulfur batteries, and the batteries also showed excellent electrochemical properties.
[0102] In summary, the present invention provides an aqueous binder modified with aloe vera gel. The binder is green, natural, cheap and easy to obtain. After modification, it can effectively inhibit the shuttle effect of polysulfide and the volume expansion of the electrode. When the positive electrode sheet prepared by the binder is assembled into a lithium-sulfur battery, the battery exhibits excellent electrochemical performance. In addition, the technical scheme also tried to modify aloe vera gel (AG) with oxalic acid (OA), D-aspartic acid (D-AA) and taurine (Taurine) to improve the performance of the binder. Except for the different acids used for modification, the remaining steps are the same as the present invention, and the mass content of the cross-linked acid is 25wt%. Preliminary results were obtained through experiments, such as Fig.10 The figure shows the electrochemical performance of the prepared lithium-sulfur battery after 300 cycles at a current density of 0.5C when AG was cross-linked and modified by OA, D-AA and Tau and used as a binder for the positive electrode of the lithium-sulfur battery. It was found that the modified aqueous binder had a certain improvement in the electrochemical performance of the lithium-sulfur battery.
[0103] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. An aloe vera gel-modified aqueous adhesive, characterized in that: Includes aloe vera gel and phytic acid; The aloe vera gel is extracted from the stems and leaves of aloe vera; The mass content of phytic acid is 5wt% to 45wt%.
2. A method for preparing an aloe vera gel-modified aqueous adhesive, used for the aloe vera gel-modified aqueous adhesive according to claim 1, characterized in that: At least the following steps are included: S1: preparing aloe vera gel, washing the stems and leaves of aloe vera, removing the tips, roots and epidermis of the aloe vera leaves, cutting them into small pieces, putting them into a juicer and blending them, letting them stand for 2 hours to defoam, filtering them with filter cloth to remove large volume residues, centrifuging them to obtain the supernatant, and then freeze-drying the supernatant for 48 hours to obtain an aloe vera gel sample; S2: cross-linking with phytic acid, cross-linking the aloe vera gel sample obtained in S1 with phytic acid, and freeze-drying the solution for 48 hours after the reaction is completed; S3: Take out the dried sample in S2, add deionized water, and stir until the aloe vera gel is completely dissolved. The mass concentration is 20 mg mL -1 of adhesive.
3. The method for preparing an aloe vera gel-modified aqueous binder according to claim 2, characterized in that: The temperature of the cross-linking reaction in S2 is 25° C. to 55° C., and the time of the cross-linking reaction in S2 is 2 h to 6 h.
4. An application of an aloe vera gel modified water-based adhesive, characterized in that: The aloe vera gel-modified aqueous binder described in claim 1 is used for preparing positive electrode plates of lithium-sulfur batteries.
5. A positive electrode plate for a lithium-sulfur battery, comprising a positive electrode active material, a conductive agent and a binder, characterized in that: The adhesive is an aloe vera gel-modified aqueous adhesive as described in claim 1.
6. A lithium-sulfur battery positive electrode according to claim 5, characterized in that: The positive electrode active material is elemental sulfur; The conductive agent includes any one of carbon black, conductive carbon and graphene.
7. A method for preparing a positive electrode sheet for a lithium-sulfur battery, used for a positive electrode sheet for a lithium-sulfur battery as claimed in any one of claims 5 to 6, characterized in that: At least the following steps are included: Mixing the positive electrode active material, the conductive agent and the binder uniformly; Add deionized water to form a slurry and stir for more than 12 hours; The slurry is then coated on a carbon-coated aluminum foil and vacuum dried at 60° C. for 24 hours to obtain a positive electrode sheet for a lithium-sulfur battery.
8. The positive electrode plate of a lithium-sulfur battery according to claim 7, characterized in that: The mass ratio of the positive electrode active material, the conductive agent and the binder is 7:2:1.